A COMPARATIVE STUDY OF THE ULTRA-VIRES RULE IN CORPORATE LAW (NATIONAL CAPITAL LAW JOURNAL, 2004)
NA
Keywords: Freedom Of Speech; Contempt Of Court; Article 19(1)(A); Reasonable Restrictions; Criminal Contempt; Scandalising The Court; Judicial Independence; Rule Of Law; Fair Administration Of Justice; Fundamental Rights.